Coordinators’ leadership styles and teachers’ perceived level of job performance and job satisfaction in primary private school in Lebanon - Hably, Farah (2022)
Leadership style is defined as a leader’ characteristic behaviours when working with a group of people. At school, coordinators might have different leadership styles they use with teachers. An effective leadership style would increase employees’ satisfaction and enhance their performance level. The purpose of this study is to investigate how teachers perceive their job performance and satisfaction according to two different leadership styles: transformational and transactional. Quantitative and qualitative data were collected through a questionnaire and an interview. Participants consisted of 31 teachers working at the elementary level in a private school in Beirut. Results were mostly comparable, showing that teachers feel satisfied and perform better when working with a coordinator who has a transformational leadership style. That is, one who recognizes that teachers have different abilities and needs, who spends time coaching and training, who communicates a common vision and mission, who projects confidence that goals can be achieved, who talks optimistically about future goals, and who gets teachers to look at problems and solve them from multiple perspectives. Further research is needed on a larger scale to confirm these results.